Phylogenetic analysis of Macroglossus Sobrinus from Peninsular Malaysia - Fauzan Ahmad, Hajar; Japning, Jeffrine Rovie Ryon; Senawi, Juliana; Kamarudin, Kamarul Rahim (Department of Wildlife and National Parks Peninsular Malaysia, 2008)
A study on the phylogeneticso f Mocroglossuss obrinus( GreaterL ong-nosedF ruit Bat)from Peninsular Malaysia was done using partial cytochrome b (cyt-b) mitochondrial DNA (mtDNA)g ene.T he specimenso f M. sobrinusw ere collectedf rom Kedah( WengU lu Muda ForestR eserve)P, erak( BintangF orestR eserve)s, elangor( Ulu Langat),M elaka (Asahan Catchment Area), Johor (Gunung Ledang), Kelantan (Gua Musang), and pahang (Krau WildlifeR eserve)T. hirty ninec yt-bs equencesin cludinge ighteens equenceso f M. sobrinus, twenty sequenceso f M. minimust aken from the GenBanka, nd a sequenceo f Penthetor /ucosi( Lucas'sS hort-nosedF ruit Bat) as an outgroup were incorporatedi n the analyses. Three main methods namely neighbourj oining (NJ) ,m aximum parsimony( Mp) , and maximuml ikelihood( ML) were usedi n the phylogenetictr ees reconstructionfo llowed by the consensusp hylogenetictr ee to summarizet he overallf indings.T he four trees were reconstructedto determinet he geneticr elationshipb etweenM . sobrinusa ndM . minimus. Generallyt,h e trees indicatedg eneticd ivergenceb etweenp opulationso f M. sobrinus.The resultw as fur,thers upportedb y very low geneticd istancesb asedo n Kimura2 -parameter distance( 1980)c alculationT. herew as an individuaol f M. sobrinus( GuaM usang,K elantan) 55 clusteredw ith the M. minimus individualst,h us indicatingo f possiblem isidentification. Apart from that, M. sobrinusf rom Kelantang avet he highestn ucleotided iversity,P 1(J ukes & Cantor1 969)w ith 0,65%,f ollowed by Perak( 0.36%),K edah( 0.27%)S, elangor( 0.78%1, and finally Pahang and Melaka with no nucleotide diversity. Overall, the nucleotide diversityo f M. sobrinusi n PeninsularM alaysiaw as 0.29%i ndicatingl ow level of genetic diversity. However, the sample size is too small to relate the results with the phylogeography and population genetic views. Therefore, more extensive studies incorporatingo ther mtDNAg enesw ith higherr ate of evolutions ucha s control regiong ene are highlyr ecommendedin the futures tudV